Answer:
The sample size is ![n = 36](https://tex.z-dn.net/?f=n%20%20%3D%2036)
Step-by-step explanation:
From the question we are told that
The sample standard deviation is ![s = 1.5](https://tex.z-dn.net/?f=s%20%3D%20%201.5)
The mean difference of the two groups is ![\=x _ 1 - \=x_2 = 1](https://tex.z-dn.net/?f=%5C%3Dx%20_%201%20-%20%5C%3Dx_2%20%3D%20%201)
The standard error is ![SE = \frac{ \= x_1 - \= x_2}{4}](https://tex.z-dn.net/?f=SE%20%3D%20%20%5Cfrac%7B%20%5C%3D%20x_1%20-%20%5C%3D%20x_2%7D%7B4%7D)
=> ![SE = \frac{1}{4}](https://tex.z-dn.net/?f=SE%20%3D%20%20%5Cfrac%7B1%7D%7B4%7D)
Let assume that the confidence level is 95% hence the level of significance is
![\alpha = (100-95)\%](https://tex.z-dn.net/?f=%5Calpha%20%3D%20%28100-95%29%5C%25)
=> ![\alpha = 0.05](https://tex.z-dn.net/?f=%5Calpha%20%3D%200.05)
So the critical value of
obtained from the normal distribution table is
![Z_{\frac{\alpha }{2} } = 1.96](https://tex.z-dn.net/?f=Z_%7B%5Cfrac%7B%5Calpha%20%7D%7B2%7D%20%7D%20%3D%201.96)
Generally the margin of error is mathematically evaluated as
![E = 0.49](https://tex.z-dn.net/?f=E%20%3D%200.49)
Generally the sample size is mathematically represented as
![n =[ \frac{Z_{\frac{\alpha }{2} * s^2}}{E}]^2](https://tex.z-dn.net/?f=n%20%3D%5B%20%5Cfrac%7BZ_%7B%5Cfrac%7B%5Calpha%20%7D%7B2%7D%20%20%2A%20s%5E2%7D%7D%7BE%7D%5D%5E2)
=> ![n = [\frac{1.96 * 1.5}{0.49} ]^2](https://tex.z-dn.net/?f=n%20%20%3D%20%5B%5Cfrac%7B1.96%20%2A%201.5%7D%7B0.49%7D%20%5D%5E2)
=> ![n = 36](https://tex.z-dn.net/?f=n%20%20%3D%2036)
<h3>
Answer:</h3>
y - 2
<h3>
Step-by-step explanation:</h3>
You get 2 less than a value when you subtract 2 from that value.
Answer:
I don't know
Step-by-step explanation:
I don't know
Answer:
The distance of the whole trip is 50 miles.
Step-by-step explanation:
Let the distance of the whole trip be x.
70% x = 35 miles
(70/100)x = 35 miles
x = 35 * (100/70) miles
x = 50 miles
Therefore, the distance of the whole trip is 50 miles.
Hope this helped!
Answer:
(2,3)
Step-by-step Explanation:
2x - y = 1
-y = -2x + 1
y = 2x - 1
4x + y = 11
4x + 2x -1 = 11
6x = 12
x=2
y=2x-1
y=2(2)-1
y=3